Use of Third-Party Indicators in Fund Reports. (Policy Papers; Policy Paper, 2017)
Fund staff use indicators developed by other organizations as input into analysis in surveillance and, to a lesser extent, in program work. While the Fund has been able to rely on data and statistics provided by member countries and compiled internally, continued efforts to foster global economic and financial stability require staff to work with indicators drawn from numerous third-party compilers. These indicators of varied qualities are used to measure concepts such as business environment, competitiveness, and quality of governance. It is anticipated that staff will continue to draw on other institutions' expertise and estimates. This practice is consistent with the Executive Board's guidance in areas where internal expertise is lacking or limited. It also puts a premium on staff's understanding of the third-party indicators (TPIs) used to add analytical value, avoid flawed conclusions and presentation, and support traction with the membership. This paper outlines a framework to promote best practice with respect to use of TPIs in Fund reports. The framework will apply to all documents that are subject to the Fund's Transparency Policy. Staff are encouraged to follow similar guidelines for other Fund documents. It draws on lessons from the current practice in the Fund and other selected international organizations (IOs), and insights from the application of an adapted data quality assessment framework (DQAF) to a subset of TPIs commonly used by Fund staff. Common good practices across IOs include the emphasis on staff judgment, review, and consultation with stakeholders.